2016
DOI: 10.1002/adsc.201600535
|View full text |Cite
|
Sign up to set email alerts
|

Facile Hydrogenolysis of C(sp3)–C(sp3) σ Bonds

Abstract: The modification of benzylic quaternary, tertiary, and secondary carbon centers through palladium‐catalyzed hydrogenolysis of C(sp3)–C(sp3) σ bonds is presented. When benzyl Meldrum's acid derivatives bearing quaternary benzylic centers are treated under mild hydrogenolysis conditions – palladium on carbon and atmospheric pressure of hydrogen – aromatics substituted with tertiary benzylic centers and Meldrum's acid are obtained with good to excellent yield. Analogously, substrates containing tertiary or second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Like N , N ‐dimethylbarbituric acid, Meldrum's acid also possesses a 1,3‐dicarbonyl core and recent articles have demonstrated its leaving group ability. A comprehensive study on hydrogenolysis of C sp3 −C sp3 bond connecting Meldrum's acid to a benzylic center of substrate 17 was carried out by Fillion and his group [18,21] . In this reaction, the carbon‐based leaving, i. e. Meldrum's acid 19 is substituted by a hydride in the presence of Pd/C and H 2 gas (Scheme 10A).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Like N , N ‐dimethylbarbituric acid, Meldrum's acid also possesses a 1,3‐dicarbonyl core and recent articles have demonstrated its leaving group ability. A comprehensive study on hydrogenolysis of C sp3 −C sp3 bond connecting Meldrum's acid to a benzylic center of substrate 17 was carried out by Fillion and his group [18,21] . In this reaction, the carbon‐based leaving, i. e. Meldrum's acid 19 is substituted by a hydride in the presence of Pd/C and H 2 gas (Scheme 10A).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive study on hydrogenolysis of C sp3 À C sp3 bond connecting Meldrum's acid to a benzylic center of substrate 17 was carried out by Fillion and his group. [18,21] In this reaction, the carbon-based leaving, i. e. Meldrum's acid 19 is substituted by a hydride in the presence of Pd/C and H 2 gas (Scheme 10A). The authors found that the CÀ C bond cleavage in substrate 17 undergoes via a hybrid S N 1/ S N 2 mechanism where initially the metal center behaves as the nucleophile.…”
Section: Meldrum's Acidmentioning
confidence: 99%
See 3 more Smart Citations